2019
DOI: 10.1038/s41598-019-47666-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered immune parameters associated with Koala Retrovirus (KoRV) and Chlamydial infection in free ranging Victorian koalas (Phascolarctos cinereus)

Abstract: Koala Retrovirus (KoRV) has been widely speculated to cause immune suppression in koalas ( Phascolarctos cinereus ) and to underlie the koala’s susceptibility to infectious disease, however evidence for immunomodulation is limited. The aim of this study is to determine whether immunophenotypic changes are associated with KoRV infection in free ranging Victorian koalas. qPCR was used to examine mRNA expression for Th1 (IFNγ), Th2-promoting (IL6, IL10) and Th17 (IL17A) cytokines, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…In this cohort of KoRV vaccinated and endogenously infected koalas, a small but significant increase in the expression of IFN-γ at both 4- and 8-weeks post-vaccination was observed, compared to pre-vaccination levels. While the biological impact of such sustained up-regulation is not fully known yet, a recent study showed that KoRV-positive southern (Victorian) koalas had significantly lowered IFN-γ levels compared to KoRV-negative koalas [ 4 ]. The authors of that study argued that such decreased IFN-γ levels may increase susceptibility to Chlamydia and other opportunistic infections in KoRV-positive koalas.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort of KoRV vaccinated and endogenously infected koalas, a small but significant increase in the expression of IFN-γ at both 4- and 8-weeks post-vaccination was observed, compared to pre-vaccination levels. While the biological impact of such sustained up-regulation is not fully known yet, a recent study showed that KoRV-positive southern (Victorian) koalas had significantly lowered IFN-γ levels compared to KoRV-negative koalas [ 4 ]. The authors of that study argued that such decreased IFN-γ levels may increase susceptibility to Chlamydia and other opportunistic infections in KoRV-positive koalas.…”
Section: Main Textmentioning
confidence: 99%
“…All northern koalas (Queensland and New South Wales) are thought to be harbour at least KoRV-A, a KoRV subtype which is both endogenous and infectious in these koala populations. KoRV infection has been linked to immune alterations, with infected southern koalas shown to have altered immune profiles [ 4 ] and KoRV-B infected northern koalas shown to possess levels of immune dysregulation [ 5 ]. KoRV has also been linked to increased susceptibility to diseases in koalas [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…KoRV is closely related genetically to gibbon-ape leukemia virus (GaLV) [ 2 , 4 ], feline leukemia virus (FeLV), and porcine endogenous retrovirus (PERV) [ 3 ]. KoRV has been linked to immunosuppression, chlamydiosis, lymphoma, and leukemia and leads to poor outcomes for infected individuals [ 4 , 7 10 ]. Progress in KoRV-related research may therefore shed light on issues that need to be tackled for any retrovirus.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Maher et al characterized the immune response to KoRV infection and found immunophenotypic changes in free-ranging Victorian koalas with significantly lower levels of IL17A and IFN-γ gene expression accompanying a significantly decreased ratio of CD4:CD8 gene expression relative to that seen in KoRV-negative koalas (Fig. 2 ) [ 10 ]. Decreased levels of IL17A and IFN-γ may render koalas more susceptible to bacterial and chlamydial infections, respectively [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation